Conventional versus digital radiography in detecting root canal type in maxillary premolars: an in vitro study. - Mahkameh Moshfeghi; Soodabeh Sadat Sajadi; Sepideh Sajadi; Majid Shahbazian (Tehran University of Medical Sciences, 2013)
Successful endodontic therapy depends on adequate mechanical and chemical debridement of the canal which requires knowledge of the canal morphology. Conventional radiography has been used to evaluate the canal type; however, direct digital radiography has recently been practiced for this purpose due to the shortcomings of conventional radiography. The aim of the present study was to compare the accuracy of digital and conventional radiography taken at 0° and 30° angles in the diagnosis of the canal type of extracted maxillary premolars.This diagnostic study was performed on 90 extracted maxillary premolars. Conventional and digital radiographies were taken of all teeth at 0° and 30° horizontal angles. The images were assessed by an oral and maxillofacial radiologist. The clearing technique was used as the gold standard. The canal type was determined using Weine classification. The agreement between each one of the 4 radiographic modalities and gold standard was determined by kappa statistics.The kappa values for the agreement of parallel conventional, 30° conventional, parallel digital and 30° digital modalities with the clearing technique were 0.059, 0.215, 0.043 and 0.391, respectively. Parallel modalities were unable to determine the tooth canal type. Radiographic images taken at 30° significantly determined the canal type, although only a poor level of agreement was noted between the two modalities and the clearing technique.All modalities had limited value to determine the root canal type in maxillary premolars. However, direct digital imaging taken at 30° angle showed the highest accuracy for canal type assessment.